Assessment by finite element modelling of the mechano-electrochemical interaction at corrosion defect on elbows of oil/gas pipelines. (15th August 2021) - Shuai, Yi; Wang, Xin-Hua; Li, Jian; Wang, Jun-Qiang; Wang, Tian-Tian; Han, Jun-Yan; Cheng, Y. Frank
Abstract: The assessment of corrosion defects to determine their effect on pipeline integrity is essential for pipe managers to develop a scientific maintenance strategy. In this work, a nonlinear finite element (FE) model coupled with multi-physical fields was developed to study the mechano-electrochemical (M-E) synergistic effect at an external corrosion defect on X100 pipeline elbow. The results indicated that bending radius has an apparent effect on the burst pressure of the corroded pipe elbow. However, anodic and cathodic reactions was insensitive to bending radius under normal working pressures. Pipes elbows with corrosion defects located in the intrados have a lower burst pressure than those in the extrados and central line crowns. When the deformation or stress generated at the corrosion defect was elastic, the synergistic mechano-electrochemical interaction effect was insignificant. However, when the depth of the defect or the applied internal pressure of the elbow was sufficient to produce a local plastic strain in the corroded region, the corrosion reaction of the local steel at the defect was remarkably enhanced. Under multiaxial stress, the corrosive behaviour of steel in the defective area involved numerous local galvanic batteries, with the anode located in the high-stress zone and the cathode in the lower-stress zone. Anodic polarisation was found to occur in high-stress zone, which accelerated local corrosion. Highlights: Developed a finite element model for corrosion defect assessment on pipe elbows. Determined the failure pressure of pipe elbows containing a corrosion defect. The location of the defect on an elbow affects the burst pressure of the pipeline. The defect depth affects the local stress and anodic current density distributions. The internal pressure affects the stress and anodic current density at the defect.